Miniaturized Microstrip Patch Antenna on YIG Material Under External Magnetic Field - Stepanyan, A.; Haroyan, H.; Hakhoumian, A.
This paper discusses an electrically small microstrip patch antenna that utilizes biased yttrium iron garnet (YIG) ferrite material. The study explores how the presence of an external magnetic field influences the bandwidth and radiation properties of the patch antenna. The antenna design is focused on operating at a frequency of 1.5 GHz. The utilization of biased YIG magnetodielectric material in the patch antenna results in an approximate threefold reduction in size compared to a patch antenna based on FR4 dielectric. Additionally, the antenna achieves a remarkable threefold increase in bandwidth, reaching 280 MHz at 1.5 GHz center frequency.
Keywords: Physics